Somatosensory and prefrontal cortex activity relates to emotional outcomes and hair cortisol concentration in chronic postsurgical pain - Margaret Moreland; Caitlin Curry; Anthony Wang; Madison Vansickel; Ziyan Wu; Christine B. Sieberg (Scientific Reports)
Abstract Chronic post-surgical pain (CPSP) poses significant socioeconomic and humanitarian challenges. This study investigated relationships between resting-state neural activation in the somatosensory cortex (SMC) and emotional functioning outcomes (depression, anxiety, perceived stress), and between prefrontal cortex (PFC) activation and chronic stress, measured by hair cortisol concentration (HCC); and whether pain intensity moderates these relationships in females with CPSP. Twenty-nine females with CPSP reported baseline pain, completed emotional functioning questionnaires, underwent functional Near-Infrared Spectroscopy, and provided hair samples for HCC analysis. Pearson’s correlation examined associations between emotional functioning and SMC activation, and between HCC and PFC activation. Benjamini–Hochberg correction adjusted for multiple comparisons. Significant correlations were further tested using moderation analyses to assess whether pain intensity influenced these associations. Left SMC activation was positively correlated with depressive symptoms (r = 0.505, pFDR = 0.036) and anxiety(r = 0.705, pFDR = 0.039). Right lateral PFC activation showed a negative correlation with HCC (r = -0.475, pFDR = 0.048). Pain intensity did not significantly moderate these relationships. Findings suggest associations between brain activity and emotional functioning in females with CPSP, highlighting potential neural targets for future interventions. This study supports the utility of multimodal approaches to further phenotype CPSP and inform precision medicine strategies.